PENGGUNAAN INFORMASI KINERJA STRATEJIK DALAM PENGAMBILAN KEPUTUSAN IMPLEMENTASI DAN PENILAIAN STRATEGI PADA ORGANISASI SEKTOR PUBLIK - Dewi Sartika (Universitas Teuku Umar, 2020)
This study investigates the role of strategic performance measures (SPM) and information system (IS) limitations in strategic decision-making and their impact on public organizational performance. Based on 180 survey responses from senior official across Yogyakarta public organizations, the study found some evidences. First, SPM of efficiency and effectiveness are positively associated with organizational performance, whereas IS limitations did not. Second, SPM of efficiency is positively associated with both strategy implementation and strategy assessment decisions, but effectiveness is only significant with strategy implementation not for strategy assessment decisions. Third, data limitations are not significantly associated with either strategy implementation or strategy assessment decisions. Finally, SPM information use for strategy implementation and strategy assessment decisions have no significant with organizational performance. Keyword: Organizational performance, Strategic Performance Measurement (SPM), Information system/data limitations, Strategic implementation decision-making, Strategic assessment decision-making, local government.